IRF6, MSX1, TGFA, dental anomalies, and skeletal malocclusion. (17th November 2020) - Fernandez, Clarissa C A; Pereira, Christiane V C A; Ferreira, Fernanda F C F; Maciel, José V B; Modesto, Adriana; Costa, Marcelo C; Vieira, Alexandre R
Summary: Objective: Verify the presence of association between four variables—transforming growth factor α ( TGFA ; C/T rs1523305), interferon regulatory factor 6 ( IRF6 ; A/C rs2013162), muscle segment homeobox 1 ( MSX1 ; A/G rs12532), and dental anomalies—with skeletal malocclusion by comparing these four variables with Angle Classes I, II, and III, and normal, hyperdivergent, and hypodivergent growth patterns. Methods: A total of 505 orthodontic records of patients older than 8 years were evaluated. The sample consisted of 285 (56.4 per cent) females, 220 (43.6 per cent) males, 304 (60.2 per cent) Whites (the rest were mixed Blacks with Whites), with a mean age of 20.28 (±10.35) years (ranging from 8 to 25 years). Eight cephalometric points, which served as the anatomical framework for obtaining angles and cephalometric measurements, were used for skeletal characterization using the Dolphin Software. Samples of saliva were collected and the DNA was extracted, diluted and quantified. Markers in TGFA, IRF6, and MSX1 were used and genotypes were obtained using TaqMan chemistry. Odds ratio (OR) and 95 per cent confidence interval (CI) calculations, chi-square, Fisher's Exact, Mann–Whitney, and correlation coefficient tests (significance level: 95 per cent) were performed. Bonferroni correction was applied and an alpha of 0.0006 was considered statistically significant. Results: There was no statistically significant associations between markers in TGFA or IRF6 with skeletal malocclusions. Tooth agenesis was associated with facial convexity ( P < 0.001). MSX1 was associated with Class II skeletal malocclusion ( P = 0.0001, OR = 0.6, CI = 0.46–0.78). Conclusion: Individuals with tooth agenesis were more likely to have a convex face. MSX1 was associated with Class II skeletal malocclusion.